Cover Image, Volume 28, Issue 9. (September 2017) - Bordignon, Stefano; Perrotta, Laura; Dugo, Daniela; Bologna, Fabrizio; Nagase, Takahiko; Fuernkranz, Alexander; Chun, K.R. Julian; Schmidt, Boris
Abstract : On the cover : The cover image, by Stefano Bordignon MD et al., is based on the Original Article Electrical isolation of the left atrial appendage by Maze‐like catheter substrate modification: A reproducible strategy for pulmonary vein isolation nonresponders?, DOI: 10.1111/jce.13276 .